Colonization and diversification shape species–area relationships in three Macaronesian archipelagos. (18th July 2018) - Price, Jonathan P.; Otto, Rüdiger; Menezes de Sequeira, Miguel; Kueffer, Christoph; Schaefer, Hanno; Caujapé‐Castells, Juli; Fernández‐Palacios, José María
ABSTRACT: Aim: Species–area relationships (SARs) on oceanic archipelagos are shaped at least as much by speciation as by immigration–extinction dynamics. We examine three well‐studied Atlantic archipelagos to quantify the relative contributions of colonization and diversification to individual and whole‐archipelago floras. Location: Three Macaronesian archipelagos: the Azores, Madeira and Canary Islands. Methods: We assessed the floras of all three archipelagos in order to compare SARs and numbers of endemic species with respect to the physical characteristics of each archipelago (geological age, isolation, and environmental diversity). Utilizing a large number of available phylogenies, we partitioned each flora into putative colonist lineages. These were used to determine: (a) the number of original colonists of each archipelago, (b) degree of relatedness among these, and (c) the degree to which internal diversification contributes to species numbers for islands and archipelagos with different physical characteristics. Results: Archipelagos varied in the parameters of the SARs in relation to their physical characteristics. The Canarian and Madeiran floras demonstrate remarkably similar SARs with z values (slopes) near 0.3, while the Azorean flora exhibits fewer species per given area and a modest z value of 0.15. The Canarian and Madeiran endemic species are concentrated in a small number of diversifying lineages, whereas the Azorean endemics were mostly in anagenetic lineages (indicating minimal internal diversification). Lineages that do not diversify within a given archipelago significantly tend not to diversify in others, whereas diversifying lineages tend to have more species in the Canarian flora when compared with related lineages in the others. Main conclusions: Although a strong independent effect of island area on species richness exists for the whole Macaronesian region, colonization and diversification are also influenced by geological age and environmental diversity of archipelagos, overriding characteristics of individual islands ("archipelago effect"). The "Azorean diversity enigma" likely results from a combination of geological youth, low environmental diversity and disproportionate human alteration.